Grandma got run over by a reindeer - Roman, Phil, 1930-; Shropshire, Elmo.; Lee, Michele; Blu, Susan; Fred Rappaport Company; Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2001)
When his beloved Grandma appears to be missing on Christmas Eve, young Jake Spankenheimer goes on the misadventure of a lifetime to try and prove that Santa Claus is indeed real.
Based on the song "Grandma got run over by a reindeer."
Special features: songwriter bio, costume gallery, grandma's guessing game, song selections, trailer.
Music, Nathan Wang.
Elmo Shropshire, narrator ; Michele Lee as Cousin Mel ; Sue Blu as Grandma ; Alex Doduk as Jake ; Jim Staahl as Santa Claus.
Not rated by the MPAA.
DVD.
Keywords: Grandmothers -- Death -- Juvenile films; Santa Claus -- Juvenile films; Children's television programs; Animated television programs; Christmas television programs; DVDs for the hearing impaired